2015
DOI: 10.1186/s12974-014-0226-z
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin regulates the Notch pathway and affects the migration and morphological transformation of activated microglia in experimentally induced cerebral ischemia in rats and in activated BV-2 microglia

Abstract: BackgroundActivated microglial cells release an excess of inflammatory mediators after an ischemic stroke. We reported previously that scutellarin effectively suppressed the inflammatory response induced by activated microglia in rats subjected to middle cerebral artery occlusion (MCAO); however, the mechanism via which scutellarin exerts its effects on microglial activation has not been explored. This study aimed to elucidate if scutellarin can regulate the Notch pathway that is linked to microglia activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 41 publications
(46 reference statements)
0
42
0
Order By: Relevance
“…We have previously shown SCU to exhibit potent biological activity, with anti-inflammatory (Wang et al, 2011), anti-oxidative (Hong and Liu, 2007), and anti-apoptotic activity (Dai et al, 2011). Importantly, SCU is able to induce Nrf2/HO-1 activity and to inhibit NF-kB signaling in hepatocytes (Zhang et al, 2018), osteoblasts (Wang et al, 2018b), and microglial cells (Yuan et al, 2015). However, the study of the value of SCU as an inhibitor of inflammation and oxidative stress in the context of OA remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown SCU to exhibit potent biological activity, with anti-inflammatory (Wang et al, 2011), anti-oxidative (Hong and Liu, 2007), and anti-apoptotic activity (Dai et al, 2011). Importantly, SCU is able to induce Nrf2/HO-1 activity and to inhibit NF-kB signaling in hepatocytes (Zhang et al, 2018), osteoblasts (Wang et al, 2018b), and microglial cells (Yuan et al, 2015). However, the study of the value of SCU as an inhibitor of inflammation and oxidative stress in the context of OA remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further confirm the effect of kellerin on regulating microglial phenotype, in vitro experiments were also carried out. The inflammatory events in ischemic brain can be simulated in vitro by exposing BV‐2 cells to cytokines (Li et al, ; Wang et al, ; Yang et al, ; Yuan et al, ). BV‐2 cells stimulated with LPS are the most popular model to mimic the microglial M1 phenotype that is induced in ischemic stroke (Han et al, ; Liu et al, ; Xiang, Xiao, Shen, & Li, ).…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacological studies have demonstrated the protective effects of STA on cerebral ischemia/reperfusion (I/R) injury because of its anti-oxidative actions and anti-apoptotic properties, as well as its ability to attenuate microglial inammatory response and neuronal damage. 4 However, the clinical outcomes of commercially available STA formulations are not as satisfactory as expected due to the low drug loading capacity, fast metabolic rate and short blood residence time of STA in vivo. 5 Moreover, STA has low solubility in both water and lipids.…”
Section: Introductionmentioning
confidence: 99%